Examining the Impact of LDR and BOPO on ROA through NIM: Evidence from Indonesian Conventional Banks (2014–2023) - Sinaga, Era Widia Br; Saajidah, Annisah; Saragih, Elisa Clara; Sirait, Melani Manginar; Hutabalian, Relli Anisma; Silaban, Putri Sari Margaret Julianty (Jurnal Ekonomi Balance, 2025)
This study investigates the influence of the Loan to Deposit Ratio (LDR) and Operating Expenses to Operating Income (BOPO) on Return on Assets (ROA), with Net Interest Margin (NIM) as a mediating variable, in Indonesian conventional banks listed on the Indonesia Stock Exchange over the 2014–2023 period. Using a quantitative approach and path analysis, the study employs panel data extracted from annual financial reports and processed with STATA 17. The findings indicate that LDR has a significant positive effect on NIM, while BOPO negatively and significantly affects NIM. In terms of profitability, LDR shows an insignificant negative influence on ROA, whereas BOPO exerts a strong negative and significant effect. Meanwhile, NIM positively and significantly impacts ROA. Mediation analysis reveals that NIM mediates the relationships between LDR and ROA, and between BOPO and ROA, with Sobel test results confirming the significance of these indirect effects. These results underscore the critical role of NIM in enhancing profitability and mitigating the adverse effects of inefficiencies. The study emphasizes the strategic importance of optimizing loan allocation and cost efficiency to improve bank performance. The findings offer practical implications for banking management in designing targeted strategies that prioritize operational efficiency and margin optimization to strengthen profitability amidst regulatory changes and increasing competition in the banking sector.